Thyroid functions, testosterone profiles and preputial microbes in cow and buffalo bulls - Bugalia, N S; Inderjeet, Inderjeet; Gulati, B R; Garg, S L; Verma, S K (The Indian Journal of Animal Sciences, 2012)
Thyroid function, testosterone levels and preputial microbial load were studied in pubertal buffalo bull calves (n=7), mature buffalo bulls (n=8) and mature cow bulls (n=6). Thyroid hormones (T3) and T4) in pubertal buffalo bull calves were comparable to breeding buffalo bulls and cow bulls, suggesting stable thyroids activity from puberty to sexual maturity for initiation of pubertal endocrine and exocrine testicular functions. Testosterone profiles, however, were distinctly low in buffalo bulls/bull calves as compared to cow bulls (P<0.05) indicating species variations and may be associated with poor libido of buffalo bulls. A variety of microbes, mostly mixed infections, were harbouring the preputial cavity of all categories of males, though slightly greater incidence was recorded in breeding cow bulls, while buffalo bull calves tended to be having relatively cleaner prepufial cavity. Escherichia coli was the most frequent isolate and the rare occurrance of Klebsiella spp. in preputial washings was also recorded in the present study.